2011
DOI: 10.1007/s11010-011-1186-6
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative and antioxidant potential of beta-ionone against benzo(a)pyrene-induced lung carcinogenesis in Swiss albino mice

Abstract: Nowadays, in developing countries like India, incidence of lung cancer is increasing rapidly, and as a consequence it has become the most common cause of malignancy-associated death. This study is aimed to evaluate the therapeutic efficacy of beta-ionone (ION), a precursor for carotenoids against benzo(a)pyrene [B(a)P]-induced lung carcinogenesis. B(a)P (50 mg/kg body weight, orally twice a week for 4 successive weeks)-induced lung cancer in mice was assessed both in tissue and serum in terms of increase LPO a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 33 publications
5
28
0
1
Order By: Relevance
“…2,6-nonadienal is most commonly used as a flavor and aroma compound by the food industries [33, 37]; and trans-beta-ionone has been reported to possess antiproliferative and antioxidant potential [38]. The presence of these beneficial compounds in the PTVO could make it a potential candidate for application in the food sector, cosmetic and pharmaceutical industries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,6-nonadienal is most commonly used as a flavor and aroma compound by the food industries [33, 37]; and trans-beta-ionone has been reported to possess antiproliferative and antioxidant potential [38]. The presence of these beneficial compounds in the PTVO could make it a potential candidate for application in the food sector, cosmetic and pharmaceutical industries.…”
Section: Discussionmentioning
confidence: 99%
“…The moderate ABTS radical scavenging activity exhibited by PTVO (Table 2) might have been due to the existence of a number of functional groups in PTVO or the stereoselectivity of the radicals, which could have affected the capacity to react and quench different radicals in the reaction medium [57]. However, the strong hydroxyl radical scavenging potential of PTVO (Table 2) could be attributed to the presence of chemical compounds such as trans-beta-ionone and benzaldehyde (Table 1), which have previously been described to possess antioxidant and antiproliferative activity [38, 58]. …”
Section: Discussionmentioning
confidence: 99%
“…The phase of reactive oxygen species (ROS) inside the lung is amplified by cigarette smoke, irritation, and toxins. Chemicals are mediators of lung carcinogenesis . Chemoprevention mediators are capable of restricting the enhancement of reactive carcinogenic metabolites, recreation of enzymes to facilitate detoxification of cancer‐causing mediators, scavenging ROS, distress apoptosis, and inhibit cell proliferation .…”
Section: Introductionmentioning
confidence: 99%
“…Rosmanic acid had demonstrated to possess potent anticancer and apoptotic effect in mouse-induced skin cancer [121], curcumin, (-)-epigallocatechin-3-gallate, and lovastatin in combination were able to suppress esophageal cancer in mouse [154], and melatonin demonstrated diminishing the development and mortality of mouse implanted with murine hepatoma cells MN22a [39]. It was demonstrated that beta-ionone, a precursor of carotenoids, ameliorated lung carcinogenesis; the latter is attributed to the antiproliferative and antioxidant potential of beta-ionone through free radical scavenging properties [9]. Α-tocopherol showed down-regulation of the expression of the stress-activated genes PKC-α, c-Myc, and Lactate dehydrogenase A (LDHA) in cancerous mice, decreasing cancer cell proliferation [120].…”
Section: Antioxidants In Cancer Assaysmentioning
confidence: 99%